Colorado water, November/December 2015 - Middleton, Lindsey A., editor; Colorado Water Institute, publisher (Colorado State University. Libraries, 2015)
Newsletter of the Colorado Water Center. Theme: Agricultural water conservation: tools, technology, and collaboration.
The newsletter is devoted to highlighting water research and activities at CSU and throughout Colorado.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado